Employability and its relationship with the competency-based approach, teaching methodologies, and assessment in higher education: a systematic review - Pérez Zúñiga, Ricardo; Martínez García, Mario; Oliva Ibarra, Francisco Eduardo (Frontiers in Education, 2025)
IntroductionThe employability of university community members depends on the skills they acquire, as well as on the teaching and evaluation methodologies used. The integration of these elements into academic programs is crucial for successful job placement.MethodsThe PRISMA methodology was followed for a systematic review of literature indexed in Web of Science and Scopus, based on a critical analysis of the literature.ResultsThe results primarily encompass undergraduate, graduate, and postgraduate. The training is predominantly multidisciplinary, emphasizing skills such as communication, teamwork, problem-solving, and critical thinking. Teaching methods utilize real-world environments, while assessments employ Likert scales and task-based evaluations.DiscussionEmployability is a key objective in higher education and should be integrated at all academic levels. The most effective teaching methods are experiential and practical, as they simulate real-world work environments. Core competencies include communication, teamwork, problem-solving, and critical thinking. In addition, newer competencies such as ethics, professionalism, and a capacity for lifelong learning are increasingly important. Finally, assessment methods must be aligned with these practical approaches.